2015
DOI: 10.3844/ajptsp.2015.27.31
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Pattern of Anti-Hypertensive Drugs in Adherence to JNC- 7 Guidelines

Abstract: Abstract:The main objective of the present study to investigate the utilization pattern of antihypertensive drugs in hypertensive patients and to find out whether the prescription pattern is in adherence with the JNC7 guidelines for the management of hypertension. A prospective study was conducted and drug utilization data were collected from 137 hypertensive patients who were attended as Out Patient Department (OPD) of Rajendra Memorial Research Institute of Medical Sciences (RMRIMS), Patna, Bihar, India. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 11 publications
6
16
1
Order By: Relevance
“…The above pattern is analogous to studies conducted by (Jhaj et al; Malhotra et al; Kothari et al; Murti et al) in India. [32][33][34][35] However the above pattern is anomalous to other studies conducted by (Tiwari et al; Surapaneni et al) in India, Pittrow et al in Germany and (Lee et al, in China have reported higher prevalence of hypertension in females than in males. 18,26,29,30 This study also reveals that hypertension is more prevalent in elderly patients belonging to age group 40-60 or more.…”
Section: Discussioncontrasting
confidence: 54%
“…The above pattern is analogous to studies conducted by (Jhaj et al; Malhotra et al; Kothari et al; Murti et al) in India. [32][33][34][35] However the above pattern is anomalous to other studies conducted by (Tiwari et al; Surapaneni et al) in India, Pittrow et al in Germany and (Lee et al, in China have reported higher prevalence of hypertension in females than in males. 18,26,29,30 This study also reveals that hypertension is more prevalent in elderly patients belonging to age group 40-60 or more.…”
Section: Discussioncontrasting
confidence: 54%
“…Our report might relate to the recent report of the high prevalence of hypertension and obesity among women in Nigeria [23]. The results indicated that most of the patients were in the age range of 41-60, which is consistent with the study by Krishna et al [22]. This shows that CVDs and diabetes affect people in the most productive years of their lives.…”
Section: Discussionsupporting
confidence: 92%
“…There was a high prescription of CCB, particularly amlodipine in FCT district hospitals. This was reported in some other studies [11,12,39,40] while CCB has been reported as least prescribed [22,41]. Agents that act on the renin-angiotensin system hold a good share of the prescription, with Lisinopril and Telmisartan leading in the class similar to other studies [15,41].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…75% were put on multidrug therapy out of which 35% patients were on two drug therapy, 32% of patients on three drug therapy and 08% on four drug therapy. 5 Among the monotherapy category the various hypertensive classes prescribed were CCB's (15%) followed by Diuretics (08%), ARB's (04%) and ACEI (02%) respectively. As a Monotherapy Amlodipine (15%) was the most frequently prescribed drug along with furosemide (08%), telmisartan (02%), losartan (02%), and ramipril (02%).…”
Section: Discussionmentioning
confidence: 99%